2020
DOI: 10.2147/ijwh.s278222
|View full text |Cite
|
Sign up to set email alerts
|

<p>Urinary Incontinence and Women CrossFit Competitors</p>

Abstract: Purpose Urinary incontinence is a common condition that potentially discourages women from participating in physical activity. This study aimed to determine the prevalence of urinary and athletic incontinence and establish which activities and contexts were most likely to provoke urine leakage in women CrossFit competitors. Patients and Methods This research was an international, cross-sectional, survey-based study. The online survey was completed by 452 women CrossFit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 23 publications
(49 reference statements)
3
18
0
2
Order By: Relevance
“…The squat was the second most likely competition lift to provoke UI in our cohort of powerlifters. While 36.3% of participants in our study reported experiencing UI during squats, comparable studies reported that 23% of weightlifters [11] and 12.6% of CrossFit participants [17] experienced leakage of urine while squatting. Squats are possibly less likely to provoke UI in weightlifters and CrossFit participants due to a difference in the amount of weight lifted, and the number of sets and repetitions performed during training or competition.…”
Section: Sport Related Factors-loadsupporting
confidence: 48%
See 2 more Smart Citations
“…The squat was the second most likely competition lift to provoke UI in our cohort of powerlifters. While 36.3% of participants in our study reported experiencing UI during squats, comparable studies reported that 23% of weightlifters [11] and 12.6% of CrossFit participants [17] experienced leakage of urine while squatting. Squats are possibly less likely to provoke UI in weightlifters and CrossFit participants due to a difference in the amount of weight lifted, and the number of sets and repetitions performed during training or competition.…”
Section: Sport Related Factors-loadsupporting
confidence: 48%
“…Most commonly UI is classified as stress (complaint of involuntary loss of urine on effort or physical exertion including sporting activities, or on sneezing or coughing [ 1 ]), urgency (complaint of involuntary loss of urine associated with urgency [ 1 ]) or mixed UI (complaint of both stress and urgency UI [ 1 ]). The term athletic incontinence is not an officially recognised term [ 17 ] but a term used either generally in the literature to describe UI experienced during athletic activity [ 18 ] or more specifically to describe UI experienced by otherwise continent young nulliparous women only during training and competition [ 19 ]. More recently, the term athletic incontinence has been used to describe UI experienced during exercise by otherwise continent women of any age or parity [ 11 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A IUE é considerada pelos artigos científicos estudados como o tipo mais comum de IU, sendo caracterizada por sintomas como a perda de urina ao tossir e/ou espirrar e em conformidade com a frequência de impacto sobre o períneo, sendo esse fato comum durante a realização de atividades físicas de alto impacto que implicam no esforço físico de mulheres (Wikander et al, 2020;Khowailed et al, 2020;Campbell, Batte, & Drummond, 2020;Sorrigueta-Hernandez et al, 2020).…”
Section: Discussionunclassified
“…Para Wikander et al (2020) a incontinência urinária é uma condição comum que potencialmente desestimula as mulheres de participarem de atividades físicas. Conforme o estudo, as atividades CrossFit de alto impacto foram mais propensas a provocar incontinência urinária.…”
Section: Discussionunclassified